Spiritualitas Berhubungan dengan Kualitas Hidup ODHA - G. Nur Widya Putra; Putu Agus Ariana; Kadek Yudi Aryawan; I Gede Prayadi Putra (Journal of Telenursing (JOTING), 2021)
This study aims to determine the relationship between the level of spirituality and the quality of life of ODHA in KDS Kosala Bali. The research design used was analytic observational with a cross-sectional approach. The research sample consisted of 60 ODHA. The technique used is non-probability sampling with saturated sampling techniques and data collection instruments using the Indonesian language WHOQOL-HIV BREF questionnaire sheet to measure the Quality of Life and the Spiritual Well Being Scale (SWBS) questionnaire sheet to analyze the level of spirituality. The results showed that there was a relationship between spirituality and the quality of life of ODHA in KDS Kosala Bali (p = 0.030, r = 0.511) with a positive direction, meaning that the higher spirituality, the better the quality of life. In conclusion, there is a relationship between the level of spirituality and the quality of life of ODHA in KDS Kosala Bali. Keywords: Quality of Life, ODHA, Spirituality